Surgical management for type II cesarean scar pregnancy - Lin Ling; Juanjuan Fu; Lei Zhan; Wenyan Wang; Qian Su; Jun Li; Bing Wei (IMR Press, 2021)
Background: Cesarean scar pregnancy (CSP), a rare type of ectopic pregnancy, can lead to adverse pregnancy outcomes. However, there is no uniform international treatment guideline for CSP. In this study, we retrospectively analyzed the advantages and disadvantages of three different surgical methods for type II CSP, trying to find the best treatment plan. Methods: From January 2013 to December 2018, a retrospective analysis was performed in 58 patients with type II CSP admitted to the Department of Gynecology, Second Affiliated Hospital of Anhui Medical University. 20 patients underwent hysteroscopic resection (Group A), 18 patients underwent laparoscopic resection and repair (Group B), and 20 patients underwent vaginal resection and repair (Group C). All patients were treated with preventive uterine artery embolization (UAE) preoperatively. The clinical data were collected, and the treatment effects of the different surgical methods were compared. Results: Age, gravidity, parity, number of previous cesarean sections, time period since the last cesarean section, menolipsis days, and preoperative level of the beta-subunit of human chorionic gonadotropin (β-hCG) were not significant different among the three groups (P > 0.05). The differences in operation time (46.85 ± 20.91 min vs. 105.78 ± 32.95 min vs. 67.85 ± 32.88 min), intraoperative blood loss (45.00 ± 17.32 mL vs. 262.22 ± 235.74 mL vs. 166.50 ± 150.66 mL), postoperative hemoglobin level decreased (11.60 ± 5.60 g/L vs. 20.11 ± 7.72 g/L vs. 14.95 ± 5.40 g/L), and menstrual cycle recovery time (35.40 ± 6.31 day vs. 30.11 ± 5.04 day vs. 30.80 ± 4.62 day) were significant different. Conclusions: Hysteroscopic, laparoscopic, and transvaginal surgery can effectively treat type II CSP. Treatment should be individualized according to the diameter of the gestational sac, the patient's fertility requirements as well as the doctor's surgical experience and the surgical equipment of the local hospital.